Porous SnO2 microsphere and its carbon nanotube hybrids: Controllable preparation, structures and electrochemical performances as anode materials. (20th August 2021) - Li, Jiwen; Yao, Wenli; Zhang, Fangcong; Rao, Xianfa; Zhang, Qian; Zhong, Shengwen; Cheng, Hongwei; Yan, Zhengquan
Highlights: Tremella-like porous SnO2 Microsphere and its CNTs hybrids are first constructed controllably under microwave radiation. They express superior lithium storage performances as anode materials. SnO2 -S/CNTs hybrids remain 470.16 mAhg –1 after 550 cycles at the current density of 1.0 Ag –1 . Synergistic effects on morphologies, structures and properties for both SnO2 -S and SnO2 -S/CNTs are illustrated. Abstract: To improve the electrochemical performance of SnO2 -based electrode materials, a simple and efficient method was developed for constructing porous SnO2 microsphere (p-SnO2 MS) and its carbon nanotube hybrids (p-SnO2 MS/CNTs), for the first time, by only changing solvent kinds under microwave-radiation conditions. After their microstructures and electrochemical properties were investigated, it is noted to find that the proposed p-SnO2 MS assembled by nano plates is mainly composed of rutile phase with a little orthorhombic phase. Among all single SnO2 materials with different morphologies, p-SnO2 MS displays a charge capacity of 860.59 mAhg –1 after 50 cycles, and a charge capacity of 593.37 mAhg –1 at the current density of 4.0 Ag –1 . Once hybridized with CNTs, the corresponding charge capacity of p-SnO2 MS/CNTs would improve to 926.58 mAhg –1 and 625.50 mAhg –1 respectively under the same conditions. Importantly, p-SnO2 MS/CNTs could deliver quite a stable charge capacity of 478.53 mAhg –1 after 600 cycles at 1.0 Ag –1 in Li/p-SnO2 MS/CNTs half cells and a high specific capacity of 738.03 mAhg –1 after 100 cycles in p-SnO2 MS/CNTs/LiNi0.5 Co0.2 Mn0.3 O2 full cells. The relationship between micro-structure and improved electrochemical performance is investigated in detail for both p-SnO2 MS and p-SnO2 MS/CNTs. This work will offer a promising insight into constructing some practical anode materials with improved lithium storage performances.